2019
DOI: 10.3390/coatings9080477
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Modification of Magnesium Hydroxide Coating Deposited Cathodically on Magnesium Alloy and its Corrosion Protection

Abstract: In this paper, hydrophobic modification of magnesium hydroxide film prepared by cathodic deposition on ME20M Mg alloy was achieved with ethanol solution of stearic acid. The effects of solution concentration, temperature and treatment time on the surface wettability were investigated. The corrosion behaviors of typical samples were evaluated by droplet test, total immersion corrosion test as well as PDP (Potentiodynamic Polarization) and EIS (Electrochemical Impedance Spectroscopy) techniques, respectively. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As a result, the future focus may be on enhancing the barrier effect and binding force for a full-life corrosion-resistant service. In this regard, composite coating may be a viable option for increasing the adhesion force of organic biopolymer coating [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Furthermore, the formation of composite coatings not only improves corrosion resistance but also endows the Mg alloys with potential bioactivity and biocompatibility in long-term tests.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the future focus may be on enhancing the barrier effect and binding force for a full-life corrosion-resistant service. In this regard, composite coating may be a viable option for increasing the adhesion force of organic biopolymer coating [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Furthermore, the formation of composite coatings not only improves corrosion resistance but also endows the Mg alloys with potential bioactivity and biocompatibility in long-term tests.…”
Section: Discussionmentioning
confidence: 99%
“…A magnification (×20,000) of zones (Figure 1c,d) suggested that there is air, probably trapped inside the micro/nanostructures of the coating, which could reduce the contact between aggressive substances and alloy surface in the air sites, providing corrosion resistance to the alloy [62]. Table 3.…”
Section: Sem-eds Analysismentioning
confidence: 99%
“…EDS elemental analysis (wt.%) of several randomly selected zone areas (Figure 1) of the PS-ZrO 2 -AM60-AlN (Zones 1-2) and PS-ZrO 2 -AM60 (Zones 3-4) tested samples. A magnification (×20,000) of zones (Figure 1c,d) suggested that there is air, probably trapped inside the micro/nanostructures of the coating, which could reduce the contact between aggressive substances and alloy surface in the air sites, providing corrosion resistance to the alloy [62].…”
Section: Sem-eds Analysismentioning
confidence: 99%
“…In this regard, a composite coating may be a possible option for increasing the adhesion force of organic biopolymer coatings [12,13]. In addition, the formation of composite coatings not only improves corrosion resistance, but also imparts potential bioactivity and biocompatibility to magnesium alloys during long-term use.…”
Section: Current Trendsmentioning
confidence: 99%